Les premières années du Salon des Humoristes à Alger (1924-1930) :: appropriation d’un modèle parisien ? - Murgia, Camilla (Manazir Journal, 2021)
My contribution focuses on the early years of the Salon des Humoristes held in Algiers in the 1920s. This event contributed to the development of caricature in Algeria in the wake of the First World War. Although it is difficult to trace the careers of all the caricaturists because of a lack of biographical information, we shall see that those present in the first editions of the Salon des Humoristes in Algiers were most often born in Europe where they trained before settling in Algeria, while some others were born in the French departments of Algeria. The first edition of the Salon des Humoristes d’Alger took place in 1924 and was hailed with success by the Algerian press. This initiative had a precedent in Paris, notably with the Salon des Humoristes held in the French capital in 1907. My paper aims to explore this echo between the Algerian and the Parisian Salon and to discuss the impact of caricature in the early years of this event. My objective is to understand to what extent the training and artistic background of the exhibitors determined and/or allowed the development of Algerian caricature and what its relationship with the Parisian exhibition was.